Confession and criminal justice in late medieval Italy: Siena, 1260-1330 - Zanetti Domingues, Lidia Luisa (Oxford historical monographs, 2021)
This monograph provides an in-depth comparison of lay and religious sources produced in Siena (1260-1330) on criminal justice, conflict, and violence.